Acute Bronchiolitis: The Less, the Better? - Virgili, Fabrizio; Nenna, Raffaella; Di Mattia, Greta; Matera, Luigi; Petrarca, Laura; Conti, Maria G.; Midulla, Fabio (Current Pediatric Reviews, 2024)
Background: Acute bronchiolitis is a viral infection of the lower respiratory tract affecting infants aged under 12 months, variably presenting with respiratory distress, diffuse crackles and inflammatory wheezing. The main causative agent is Respiratory Syncytial Virus (RSV). The diagnosis is clinical and treatment mainly supportive. Despite the availability of more than 30 international guidelines, consistent management recommendations are lacking and considerable variability in patients’ care persists among different providers. Objective: To review and describe current knowledge about epidemiology, physiopathology, clinic, diagnosis and management of acute bronchiolitis, with particular emphasis on updated evidence and future perspectives in terms of treatment and prevention. Methods and Results: We searched Cochrane for systematic reviews and PubMed for scientific articles published in the last 10 years, using a combination of the following search terms:
Keywords: guideline